2022
DOI: 10.3390/app12199401
|View full text |Cite
|
Sign up to set email alerts
|

Rosa davurica Pall., Rosa rugosa Thumb., and Rosa acicularis Lindl. Originating from Far Eastern Russia: Screening of 146 Chemical Constituents in Three Species of the Genus Rosa

Abstract: Rosa rugosa Thumb., Rosa davurica Pall., and Rosa acicularis Lindl. contain a large number of target analytes which are bioactive compounds. High performance liquid chromatography (HPLC), in combination with the ion trap (tandem mass spectrometry), was used to identify target analytes in MeOH extracts of R. rugosa, R. davurica, and R. acicularis, originating from the Russian Far East, Trans-Baikal Region, and Western Siberia. The results of initial studies revealed the presence of 146 compounds, of which 115 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…The fragment ion with m/z 146.19 yields two daughter ions at m/z 144.19 and m/z 118.23. It has been identified in the bibliography in extracts from Huolisu Oral Liquid [7], Rosa acicularis [8], Camellia kucha [9], Euphorbia hirta [10], Hylocereus polyrhizus [11], and rapeseed flower petals [12]. The CIDspectrum in positive ion modes of atractylenolide II from extracts of A. martjanovii from the Botanical Garden of NEFU are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…The fragment ion with m/z 146.19 yields two daughter ions at m/z 144.19 and m/z 118.23. It has been identified in the bibliography in extracts from Huolisu Oral Liquid [7], Rosa acicularis [8], Camellia kucha [9], Euphorbia hirta [10], Hylocereus polyrhizus [11], and rapeseed flower petals [12]. The CIDspectrum in positive ion modes of atractylenolide II from extracts of A. martjanovii from the Botanical Garden of NEFU are shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…is well known in northeastern Asia as a food source enriched with vitamins C and E [ 13 ]. Various therapeutical effects of R. davurica have been identified, such as antioxidant, anti-HIV, antiviral, antibiotics, and hypoglycemic activities [ 14 ]. Our previous study demonstrated the antioxidative and photoprotective effects of R. davurica leaf extract on in vitro human keratinocytes models [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the plant's flowers contribute to the formulation of perfumes and cosmetic products. Notably, the leaves and fruits of R. davurica boast a richness in ascorbic acid, commonly recognized as vitamin C, endowing them with notable properties, such as antioxidant, anticancer, and anti-aging effects [7,8]. A recent study revealed that a 30% ethanol extract from R. davurica inhibited UVB-induced photoaging [9].…”
Section: Introductionmentioning
confidence: 99%